Comparative analysis of corneal parameters in simple myopic anisometropia using Scheimpflug technology - Wang, Di; Chang, Yue; Nan, Weijin; Zhang, Yan (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose: This study aims to investigate the differences in binocular corneal parameters and their interrelation with binocular biometric parameters asymmetry in patients with simple myopic anisometropia, thereby elucidating the influence of myopia process on various corneal parameters.In this cross-sectional study, 65 patients with anisometropia in monocular myopia were included. They were divided into low anisometropia group：-3.00D＜Δ spherical equivalent (SE)≤-1.00D (Δ represents the difference between the two eyes, i.e. myopic data minus emmetropic data) and high anisometropia group: ΔSE≤-3.00D. Corneal and ocular biometric parameters were measured using Pentacam, Corvis ST, and IOL Master 700. Statistical analyses focused on the binocular corneal parameters asymmetry, using the contralateral emmetropia as a control.The mean age of participants was 18.5±1.3 years, with the average SE for myopia and emmetropia being -2.93±1.09D and -0.16±0.41D, respectively. The central corneal thickness (CCT), flat keratometry (Kf), keratometry astigmatism (Ka), total corneal aberration (6mm) (TOA), surface variance index (ISV), vertical asymmetry index (IVA), stress-strain index (SSI), and first applanation stiffness parameter (SPA1) and ambrosia relational thickness-horizontal (ARTh) showed significant differences between anisometropic fellow eyes (P<0.05). There were significant differences in ΔIVA, Δ the difference between the mean refractive power of the inferior and superior corneas (I-S), Δ deviation value of Belin/Ambrósio enhanced ectasia display (BAD-D), Δ deformation amplitude ratio max (2mm) (DAR)and Δ tomographic biomechanical index (TBI) (P<0.05) in two groups. Asymmetry of corneal parameters was correlated with asymmetry of ocular biometric parameters. Anisometropia (ΔSE) was positively correlated with ΔIVA (r=0.255, P=0.040), ΔBAD-D (r=0.360, P=0.006), and ΔSSI (r=0.276, P=0.039) and negatively correlated with ΔDAR (r=-0.329, P=0.013) in multiple regression analysis. Δ mean keratometry (Km), Δ anterior chamber depth (ACD), and Δ biomechanically corrected intraocular pressure (bIOP) were also associated with binocular corneal differences. Conclusion: Compared to contralateral emmetropia, myopic eyes have thinner corneas and smaller corneal astigmatism. Myopic corneas exhibit relatively more regular surface morphology but are more susceptible to deformation and possess marginally inferior biomechanical properties. In addition, there is a certain correlation between anisometropia and corneal parameter asymmetry, which would be instrumental in predicting the development of myopia.